Wearable Supercapacitive Temperature Sensors with High Accuracy Based on Ionically Conductive Organogel and Macro‐Kirigami Electrode. Issue 4 (20th November 2022) - Yu, Yuyan; Peng, Shuhua; Islam, Mohammad; Wu, Shuying; Wang, Chun H.
Abstract: Wearable temperature sensors with high accuracy are critical for human health monitoring. Ideally, they should show accuracy matching that of medical‐grade thermometers (i.e., ± ≈0.1–0.2 °C). Achieving this goal has proven challenging for sensors that must also meet key wearable requirements, such as flexibility, stretchability, and breathability. Herein, a new stretchable supercapacitive temperature sensor with a resolution of ±0.2 °C, is presented, which was achieved by. Two new strategies to increase temperature sensitivity and minimize the interferences of mechanical stretching and pressure: a) synthesizing an ion‐conductive NaCl‐organogel to serve as the redox‐active separator to increase sensitivity and suppress interference of compression; and b) using a kirigami design to decrease the interference of stretch and improve breathability. These two novel strategies endow the supercapacitive temperature sensors with a temperature accuracy of ±0.2 °C and exceptionally high sensitivity of 0.095 °C −1, which is more than 13 times higher than traditional dielectric‐capacitive sensors. The potential of the supercapacitive sensor in measuring body temperature is demonstrated by continuously monitoring skin temperatures under a medical compression garment that exerts pressure on the skin and the unsteady wrist flexion. The findings confirm that the organogel‐based supercapacitive sensors offer an extraordinary temperature accuracy significantly better than wearable sensors reported in the literature. The combined characteristics of high resolution, linearity, breathability, and stretchability make this sensor a promising candidate for skin‐interfaced health monitoring devices. Abstract : A stretchable and flexible temperature sensor with high accuracy is achieved by a) synthesizing an ion‐conductive NaCl‐organogel to serve as the redox‐active separator to suppress interference of compression. b) Using a kirigami design to decrease the interference of stretching. The designed sensor has a resolution of ±0.2 °C, approaching the medical‐grade thermometers.